The Sage dictionary of criminology - McLaughlin, Eugene 1959-; Muncie, John (Sage, 2019)
A reference tool for students of criminology and criminal justice, this book provides an accessible introduction to key theories, concepts and topics, offering comprehensive guidance through the field. It contains thirty-six entries, covering subjects such as anti-social behaviour, globalization, human trafficking and terrorism.